2021
DOI: 10.1111/jgs.17078
|View full text |Cite
|
Sign up to set email alerts
|

Community health worker interventions for older adults with complex health needs: A systematic review

Abstract: Background/Objectives The number of older adults with complex health needs is growing, and this population experiences disproportionate morbidity and mortality. Interventions led by community health workers (CHWs) can improve clinical outcomes in the general adult population with multimorbidity, but few studies have investigated CHW‐delivered interventions in older adults. Design We systematically reviewed the impact of CHW interventions on health outcomes among older adults with complex health needs. We searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 56 publications
3
17
0
Order By: Relevance
“…Thus HMrs contribute to the opening and continuity of health coverage rights, access to care, and the reception of persons by raising the awareness of medico-social professionals, and to developing tools for health professionals [15]. HMrs create links between patients and healthcare professionals, and participate in a change of representations between the health system and a population that, because of its di culties, does not manage to access the system [10,16,17]. To our knowledge, only few studies have reported experience with or evaluated this intervention mode in emergency departments (EDs), even though they are highly concerned by persons in precarious situations [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Thus HMrs contribute to the opening and continuity of health coverage rights, access to care, and the reception of persons by raising the awareness of medico-social professionals, and to developing tools for health professionals [15]. HMrs create links between patients and healthcare professionals, and participate in a change of representations between the health system and a population that, because of its di culties, does not manage to access the system [10,16,17]. To our knowledge, only few studies have reported experience with or evaluated this intervention mode in emergency departments (EDs), even though they are highly concerned by persons in precarious situations [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…FITxOlder was based on lessons learned from a previous pilot study that used an iterative process to gather input from a work group of Latino older adults in developing and tailoring the delivery of the FITxOlder program as well as the Five Animal Frolics routines [ 38 ]. For example, participants were appreciative of the group format that offered opportunities for socialization and peer support in FITxOlder [ 58 , 59 ] and the program delivery by a bilingual CHW who provided linguistically and socially sensitive support to engage the participants [ 60 ]. The findings also reflect older adults’ interest in improving quality of life and independent living beyond health indexes [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of making sustainable changes to prevent future fall events was similar between groups and both groups had a similar number of post-discharge hospitalizations. In older adults, interventions used by community health workers to decrease fall risk varied by study, were more often multifactorial, and typically included education and environmental modifications (Kennedy et al, 2021; Lee & Yu, 2020). For community-living adults 65 years and older, environmental factors were consistently identified as a primary causal factor in fall events and injuries sustained from falls (Adams et al, 2020; Stamm et al, 2016; Verma et al, 2016).…”
Section: Discussionmentioning
confidence: 99%